(3CYjGf GdYUQ hGYhGf GdfUQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO GdPi Mce Ydi Cgd GdhLhO HGdbOQ de CLQ ZGjI ecQi efg ai Uag s
(3BNQgG (B:s
(3hSNW HPdc cKjQG hdeG YGO bGe HOeTb hJhai hCYWi NHQI ddCejQ eMi GdOjf fLR GdeLdO GdChd s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdChds
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B53s
(3Chdg agQS ddJQGLes
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B24 s
Keywords: (3GdJGQjNs